Students’ improvement in writing skill using column comment on Facebook group - Novarita Novarita; Nurul Afifah; Awalludin Awalludin; Miranda Miranda (Concept : Community Concern for English Pedagogy and Teaching, 2022)
The objective of this case study is to investigate the effect of using the comment section on a Facebook group on increasing the writing ability of students at MA Pondok Pesantren Nurul Islam Seri Bandung. The study aims to determine whether utilizing the comment section can improve students' performance in writing and specifically, the material used is recount text. The participants of this study were all pupils in grade 10, with a total of 49 students. A sample of 15 students was selected through purposive sampling for the treatment class. Data was collected through a writing test consisting of 1 item and analyzed using the paired sample t-test in SPSS 22. The average pre-test score was 51.313, and the average post-test score was 85.167. The results of the data analysis showed that using the comment section on a Facebook group was significantly successful in enhancing the writing skills of students at MA Pondok Pesantren Nurul Islam Seri Bandung. Therefore, the writerss accept the alternative hypothesis (Ha) and reject the null hypothesis (Ho) as the sig. (2-tailed) = 0.000 is less than the significance level (=0.05), indicating that the use of the comment column on a Facebook group was significantly beneficial in enhancing students' ability to write recount texts at MA Pondok Pesantren Nurul Islam Seri Bandung. Keywords: Facebook; writing skill